Perancangan Jaringan Hotspot RT/RW Net Pada Desa Suka Negeri - Fikri Ya'afi Mustika; Syahril Rizal (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
RT/RW Net hotspot network is a computer network for the community in the RT/RW environment that uses wireless or cable media, hotspots are public communication tools that can be accessed freely. RT/RW Net is the best solution to provide an internet network access service in rural areas at a relatively cheaper price. In building an RT/RW net network, several network devices are needed, namely modems, mikrotik, routers/access points, and also lan cables. Mikrotik is a routerboard operating system that has the ability to manage a network. With the RT/RW Net hotspot network, it is hoped that it will make it easier for people to access the internet network.